2012
DOI: 10.1111/j.1442-2050.2012.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia detection rate of confirmatory EGD in nondysplastic Barrett's esophagus

Abstract: Current guidelines for endoscopic surveillance of Barrett's esophagus (BE) recommend that patients with newly diagnosed BE undergo confirmatory esophagogastroduodenoscopy (EGD) to exclude the presence of dysplasia. The extent to which confirmatory endoscopy alters management and detects missed dysplasia in newly diagnosed BE has not been reported. The frequency with which confirmatory endoscopy changed surveillance management in patients with newly diagnosed BE was assessed. A two center cohort analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In cases of persistence (i.e., LGD present at a second, confirmatory endoscopy) (136), there is evidence to suggest that these patients may be at higher risk, as the “SURF” study (30) demonstrated that persistence of LGD over time in the control group was predictive of progression. In such patients, the risks and benefits of therapy need to be carefully evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of persistence (i.e., LGD present at a second, confirmatory endoscopy) (136), there is evidence to suggest that these patients may be at higher risk, as the “SURF” study (30) demonstrated that persistence of LGD over time in the control group was predictive of progression. In such patients, the risks and benefits of therapy need to be carefully evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the patient phenotypic characteristics of LGD in BE (e.g., focal vs. multifo-cal, short segment vs. long segment, persistent over time vs. intermittent (i.e., found at a second confirmatory endoscopy (136) at a surveillance interval of 6–12 months), consensus pathological agreement, and so on) have variably been described as important in predicting progression (29), while Wani et al (52) followed up more than 200 patients with BE and LGD for >6 years (mean) and found that none of these variables predicted histological progression. There are several studies that indicate that patients with persistent, multifocal LGD in a longer segment of BE are more likely to progress to EA (131,136) and Thota et al (138) found a correlation between multifocality of LGD and progression of neoplasia (EA) in a single-center experience of over 1,500 patient-years and a 6% decreased likelihood of dysplastic regression per 1 cm increase in BE length. Moreover, recently, Phoa et al (30) in a large RCT demonstrated that persistence of LGD over time and length of BE was predictive of progression in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Abdalla and colleagues reported this association in their cohort of missed dysplasias as well. [18] Other studies have found that adherence to biopsy protocol decreases in patients with longer BE, resulting in a lower detection rate of dysplasia/EAC. [2,3] Although our overall rate of adherence was poor (41%), adherence did not significantly differ between the groups with and without missed dysplasia/EAC, raising the question of sampling error.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, incidence of EAC is increased in BE with high-grade dysplasia (HGD) compared with nondysplastic BE (NDBE) (5, 6). Currently, dysplasia is the only clinical biomarker that is commonly used to stratify risk in BE (7, 8, 9). Patients with BE undergo periodic endoscopic surveillance to detect dysplasia and adenocarcinoma, but it is unclear whether this practice is beneficial (10, 11, 12).…”
Section: Introductionmentioning
confidence: 99%